(untitled) (Confluenţe Bibliologice, 2012)
The article contains information about the Romanian architect Ion Mincu (1852-1912), his contributions regarding formation of modern architecture. The most important works are: Central girls School-1890; Galati Administrative Palace – 1904; Commerce Bank of Craiova; „The buﬀet” or „Romanian Pub” in Bucharest – 1892; Lahovary homes, Monteoru and Vernescu; Gheorghieﬀ families tombs, Cantacuzino and Ghica from Belu cemetery; the design of the Cathedral furniture from Constance etc.